(untitled) (Educação em Revista, 2023)
The provision of Sex Education in schools can significantly contribute to the reduction of violences motivated by issues related to gender and sexuality. This Sex Education needs to go beyond purely biological issues, addressing several other themes, such as body, pleasure, consent and violence in addition to the more obvious issues of gender, sexuality and diversity. However, in order to carry it out, teachers need to have the support of official documents and legislation. This reseach aims to verify how issues concerning Sex Education, gender and sexuality appear in laws, decrees and other publications that guide Brazilian Education, as well as to relate them to the socio-political contexts in which they were published. For this, we carried out a documentary and bibliographic research covering the period from 1990 to 2018, and we focused our analysis on twenty-eight of them. The analysis showed that, in fact, the legislation not only allows, but determines that Sex Education must carried out in schools. However, the different political contexts have a great impact on the way in which Sex Education appears in the documents, sometimes explicitly, sometimes subjectively and diluted in the discourse of diversity and, recently, completely silenced. In addition, recurrent cycles of advances and setbacks in different political contexts since redemocratization have culminated in gaps and discontinuities in Sex Education policies, without the development of a specific law on the subject, preventing its consolidation within Brazilian schools.